2019
DOI: 10.1111/cod.13225
|View full text |Cite
|
Sign up to set email alerts
|

Piroxicam‐induced fixed drug eruption: Cross‐reactivity with meloxicam

Abstract: Background: Non-steroidal anti-inflammatory drugs constitute a main cause of fixed drug eruption (FDE). A few cases of piroxicam-induced FDE have been reported; however, the crossreactivity among oxicams has rarely been evaluated.Objectives: To describe a series of patients with piroxicam-induced FDE, mostly confirmed by a positive patch test reaction, in whom cross-reactivity to meloxicam was assessed. Methods:We included all cases of piroxicam-induced FDE diagnosed in the department of pharmacovigilance of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…In a study of 30 patients with open patches on lesional skin, a positivity rate of 86.7% was reported, mostly to phenazone salicylate (16 of 16 tested) and carbamazepine (3 of 3 tested), and doxycycline (2 of 3 tested) [ 18 ]. In smaller studies, high rates of positivity to piroxicam (85.7% in one study, 6 of 7 patients) [ 69 ] and antibiotics (beta-lactams, fluoroquinolones and sulfonamides) (50%, corresponding to 4 of 8 patients) have also been reported [ 61 ]. There are numerous case reports of patch test positivity in the setting of FDE to other drugs, including fluconazole [ 70 72 ], adalimumab [ 73 ], etoricoxib [ 74 78 ], piroxicam [ 69 , 79 , 80 ], nimesulide [ 81 – 83 ], and contrast medium [ 84 , 85 ].…”
Section: Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 30 patients with open patches on lesional skin, a positivity rate of 86.7% was reported, mostly to phenazone salicylate (16 of 16 tested) and carbamazepine (3 of 3 tested), and doxycycline (2 of 3 tested) [ 18 ]. In smaller studies, high rates of positivity to piroxicam (85.7% in one study, 6 of 7 patients) [ 69 ] and antibiotics (beta-lactams, fluoroquinolones and sulfonamides) (50%, corresponding to 4 of 8 patients) have also been reported [ 61 ]. There are numerous case reports of patch test positivity in the setting of FDE to other drugs, including fluconazole [ 70 72 ], adalimumab [ 73 ], etoricoxib [ 74 78 ], piroxicam [ 69 , 79 , 80 ], nimesulide [ 81 – 83 ], and contrast medium [ 84 , 85 ].…”
Section: Bodymentioning
confidence: 99%
“…In smaller studies, high rates of positivity to piroxicam (85.7% in one study, 6 of 7 patients) [ 69 ] and antibiotics (beta-lactams, fluoroquinolones and sulfonamides) (50%, corresponding to 4 of 8 patients) have also been reported [ 61 ]. There are numerous case reports of patch test positivity in the setting of FDE to other drugs, including fluconazole [ 70 72 ], adalimumab [ 73 ], etoricoxib [ 74 78 ], piroxicam [ 69 , 79 , 80 ], nimesulide [ 81 – 83 ], and contrast medium [ 84 , 85 ]. The importance of the test vehicle for certain drugs is highlighted in a few studies by Ozkaya-Bayazit et al In one study of 27 patients with cotrimoxazole-induced FDE and 20 healthy controls, no positive results were obtained when testing with petrolatum, but 25 of 27 tested patients (92.6%) exhibited positivity when the drug was tested in varying concentrations in DMSO [ 86 ].…”
Section: Bodymentioning
confidence: 99%
“…These advanced strategies include solid dispersion, pellets, floating systems, liposomes, micro emulsions, liquid crystals, solid dispersions and nanoparticles/ nanocrystals (Goke et al, 2018;Khan et al, 2020). Piroxicam is a nonsteroidal anti-inflammatory drug, used in moderate to severe pain, rheumatoid arthritis, osteoarthritis, ankylosing spondylitis and fever (Ben Romdhane et al, 2019). PC belongs to BCS Class II which have poor water solubility and strong permeability across the cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Although medications of any class can cause FDE, NSAIDs are responsible for 51.2% of cases 2 . Furthermore, it is important to reinforce that there might be a cross‐reaction between drugs of the same class 4 . Piroxicam is an NSAID derived from the oxicams with anti‐inflammatory, analgesic, antipyretic and antiplatelet properties.…”
Section: Introductionmentioning
confidence: 99%
“…2 Furthermore, it is important to reinforce that there might be a cross-reaction between drugs of the same class. 4 Piroxicam is an NSAID derived from the oxicams with anti-inflammatory, analgesic, antipyretic and antiplatelet properties. Adverse reactions to piroxicam are not rare, and previous studies indicated piroxicam as the culprit drug of 1.6% to 12% of FDE cases.…”
mentioning
confidence: 99%